Liraglutide inhibits the proliferation of rat hepatic stellate cells under high glucose conditions by suppressing the ERK signaling pathway - Bingge Fan; Lingbing Meng; Xiao Zheng; Lei Bai; Yaping Du; Haiyan Ding; Yu Chen; Yuna Zhang (Scientific Reports)
Abstract Liver fibrosis is a common complication of diabetes. Due to the crucial role of HSCs in the pathogenesis of hepatic fibrosis, they are considered a key target in anti-fibrosis research. We designed this experiment to investigate the effects of liraglutide on the proliferation of rat hepatic stellate cells under high glucose conditions and its relationship with the extracellular regulated protein kinases (ERK) signaling pathway. Rat hepatic stellate cells were randomly assigned to five groups: the normal glucose control group, the high glucose control group, the high osmotic group, the high glucose + liraglutide group (referred to as the liraglutide group), and the high glucose + inhibitor group referred to as the inhibitor group). The five groups of cells were cultured for 48 h before proceeding with the subsequent procedures. First, the ELISA method was employed to quantitatively measure the concentration of type I collagen in the supernatant from the rat hepatic stellate cell culture. Subsequently, RT-PCR was utilized to assess the expression level of ERK mRNA in the rat hepatic stellate cells. Finally, Western blot analysis was performed to detect the expression of ERK and phosphorylated ERK (p-ERK) proteins. The proliferation of rat HSCs was significantly increased in the high glucose group compared to the normal glucose group (P < 0.05). In the liraglutide group, after 48 h of treatment, cell proliferation was reduced relative to the high glucose group (P < 0.05), although it remained higher than that of the normal glucose group (P < 0.05) and the inhibitor group (P < 0.05). No statistically significant difference in proliferation was observed between the hypertonic group and the normal glucose control group (P > 0.05). Comparison of Type I Collagen Content: There was no significant change in Type I collagen content in the hypertonic group compared to the control group (P > 0.05). However, a significant increase in Type I collagen content was observed in the high glucose group (P < 0.05). Both the liraglutide group and the inhibitor group exhibited a significant decrease in Type I collagen content compared to the high glucose group (P < 0.05). Furthermore, the Type I collagen content in the inhibitor group was lower than that in the liraglutide group (P < 0.05). Comparison of ERK mRNA Expression Levels: Compared to the control group, the hyperosmolar group exhibited no significant change in ERK mRNA expression (P > 0.05). In contrast, the high glucose group significantly increased ERK mRNA expression (P < 0.05). Both the inhibitor group and the liraglutide group showed significantly lower ERK mRNA expression levels compared to the high glucose group (P < 0.05), with the inhibitor group presenting lower expression than the liraglutide group (P < 0.05). P-ERK Expression Results: When compared to the control group, the hyperosmolar group displayed no significant change in p-ERK expression (P > 0.05). The high glucose group, however, exhibited a significant increase in p-ERK expression (P < 0.05). Both the liraglutide group and the inhibitor group had significantly reduced p-ERK expression compared to the high glucose group (P < 0.05), with the inhibitor group showing a further reduction in p-ERK expression relative to the liraglutide group (P < 0.05). Hyperglycemia promotes the proliferation of rat hepatic stellate cells. Liraglutide inhibits the proliferation of HSCs in high glucose conditions by inhibiting the ERK signaling pathway.